Determination of thermal diffusivity of Montmorillonite containing silver nanoparticles - Zamiri, Reza; Zakaria, Azmi; Ahmad @ Ayob, Mansor; Darroudi, Majid; Shameli, Kamyar; Mahdi, Mohd Adzir (National Institute of Research and Development for Optoelectronics, 2010)
The thermal lens (TL) technique is used to study thermal diffusivity of silver nano-fluid containing silver nanoparticles (Ag-NPs) of a particular size from about 30.5 to 4.2 nm at Montmorillonite (MMT) as an inorganic matrix in aqueous solution. In this technique a diode laser (wavelength 514 nm, power 80mW) and intensity stabilized He-Ne laser were used as the excitation source and probe beam, respectively. Experimental results showed that the thermal diffusivity values of nanofluids decreases when the particle size of Ag-NPs decreases.